2006
DOI: 10.1029/2005gl025472
|View full text |Cite
|
Sign up to set email alerts
|

Strong shaking in Los Angeles expected from southern San Andreas earthquake

Abstract: The southernmost San Andreas fault has a high probability of rupturing in a large (greater than magnitude 7.5) earthquake sometime during the next few decades. New simulations show that the chain of sedimentary basins between San Bernardino and downtown Los Angeles form an effective waveguide that channels Love waves along the southern edge of the San Bernardino and San Gabriel Mountains. Earthquake scenarios with northward rupture, in which the guided wave is efficiently excited, produce unusually high long‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 16 publications
(18 reference statements)
8
123
0
Order By: Relevance
“…Nevertheless, this reflects the potential long geographical reach of hazard influences, which are not reflected in the evaluation metrics presented above. For example, it has been shown that earthquakes on the San Andreas (Coachella) rev can efficiently channel long-period ground motions into the greater LA basin (e.g., Olsen et al, 2006), so a hazard map for such shaking might show consequential gains in this highly populated area. This also exemplifies how conclusions will depend on the exact hazard metric.…”
Section: Hazard Map Ratiosmentioning
confidence: 99%
“…Nevertheless, this reflects the potential long geographical reach of hazard influences, which are not reflected in the evaluation metrics presented above. For example, it has been shown that earthquakes on the San Andreas (Coachella) rev can efficiently channel long-period ground motions into the greater LA basin (e.g., Olsen et al, 2006), so a hazard map for such shaking might show consequential gains in this highly populated area. This also exemplifies how conclusions will depend on the exact hazard metric.…”
Section: Hazard Map Ratiosmentioning
confidence: 99%
“…In particular, areas characterized by low wavespeed sedimentary basins may show a very different ground response compared to hardrock sites, with strong amplifications, multiple reverberations, and prolonged shaking (e.g., Rovelli et al, 2001;Olsen et al, 2006;Chaljub et al, 2007;Lee et al, 2008). Moreover, these effects can be intensified and complicated by topographic ridges, which can cause amplifications, reflections, and multipathing (e.g., Lee et al, 2008;).…”
Section: Simulations With a 3d Model: Effects Of Geological Structuresmentioning
confidence: 99%
“…One approach for improving hazard estimates is to simulate the wave propagation through realistic 3D crustal models (Olsen et al, 1995(Olsen et al, , 2006Komatitsch et al, 2004;Graves et al, 2008). If seismograms can be simulated for sufficiently large samples of probable ruptures, then hazard curves of exceedance probability versus seismic intensity can be constructed from the calculated site response.…”
Section: Introductionmentioning
confidence: 99%